2022
DOI: 10.1007/s40122-022-00462-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking Cessation on Acute Pain: A Systematic Review

Abstract: Smoking is a known risk factor for developing various pain-related disorders. However, acute pain often triggers the craving for cigarette consumption, resulting in a positive feedback mechanism. In addition, there is evidence of decreased pain tolerance during the early stages of abstinence. Therefore, in this study, we aimed to investigate whether a period of decreased pain tolerance and increased pain intensity occurs during smoking cessation. A systematic literature search was conducted through PubMed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Likewise, we may have not included other potential confounding variables, including information regarding the co-occurrence of various non-opioid substance use disorders. For smoking, for example, an interdependency with pain perception is frequently reported [ 47 ]. Assessing data on addictive behavior is however a methodological challenge, with a great chance of misinformation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we may have not included other potential confounding variables, including information regarding the co-occurrence of various non-opioid substance use disorders. For smoking, for example, an interdependency with pain perception is frequently reported [ 47 ]. Assessing data on addictive behavior is however a methodological challenge, with a great chance of misinformation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed the mechanisms by which smoking contributes to LBP and RA. Smoking reduces blood supply to the intervertebral discs, resulting in degenerative changes and LBP [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the mechanisms by which smoking contributes to LBP and RA. Smoking reduces blood supply to the intervertebral discs, resulting in degenerative changes and LBP [7]. Moreover, smoking has been shown to elevate the levels of proinflammatory cytokines, which transmit signals to the nervous system and amplify pain [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports present the smoking rate among pain patients to exceed that of people who do not smoke 2 . Furthermore, individuals experiencing pain, such as people who smoke, tend to smoke more frequently than their pain-free counterparts 3 . The pain leads to a craving for smoking, which has a temporary analgesic effect 4 .…”
Section: Introductionmentioning
confidence: 99%